ROLUL SERVICIILOR BIBLIOTECARE PENTRU PROMOVAREA UNEI COMUNITĂȚI INCLUZIVE PENTRU COPIII ȘI TINERII CU NEVOI SPECIALE - MOLDOVANU, bibliotecar principal, Filiala de Arte „T. Arghezi”, Anastasia (BIBLIOPOLIS, 2020)
The paper is about our reality. The author wants to make a contribution identifying some aspects of the social inclusion in our environment, based on the personal observation. The „T. Arghezi” Branch has a very good collaboration with the Centre of socialization and child development „Atenţie”. The author thinks that the library has the role of intermediary coordinator and distributor of the information. There are many ways for social inclusion through libraries, but they require first of all knowledge and specific forms of activity, specific skills and competences necessary in relation with this type of users. Therefore, for librarians working with such users must be organized trainings, workshops, conferences etc.